Faktor Pendorong dan Faktor Penarik Wisatawan Surabaya Melakukan Perjalanan Wisata Ke Penang,Malaysia - Lay, Olivia Dianty (Tourism Retailing+, 2013)
This study is aimed to analyze the push and pull factors that motivate the tourists from Surabaya to travel to Penang, Malaysia. The respondents are tourists from Surabaya aged above 18 years old who have traveled to Penang within the last 1 year. Quesionnaires were used to collect data and factor analysis tecnique was used to analyze and describe the result of the research.The results of factor analysis shows that the push factors to travel to Penang are Novelty & KnowledgeâSeeking, Rest & Relaxation, Fulfilling Dream, Adventure & Cultural-Seeking, and Prestige. While the pull factors are Safety, Cleanliness, & Variety of Attraction; Events & Activities, Affordable Price, and Travel Arrangement. Based on the result of component transformation matrix, it can be concluded the push factor that dominantly motivated tourists from Surabaya to travel to Penang is Adventure & Exploration (0,733) and the pull factor that dominantly motivate tourists from Surabaya is Tour Arrangement (0,847).